2018
DOI: 10.1039/c8ra03361g
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced biohydrogen production from nutrient-free anaerobic fermentation medium with edible fungal pretreated rice straw

Abstract: An edible fungal pretreatment of rice straw was proposed for enhanced hydrogen production while reducing the chemical cost for traditional biological hydrogen production from lignocellulose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Both the adapted and parental strains reduced the cellulose mass fraction by only about 3%. Similar levels of microbially-induced degradation have been observed by others; for example, using chemical composition analysis of rice straw, Sheng et al (2018) demonstrated that lignin removal was up to 22.4%, and cellulose and hemicellulose loss was 13.3% and 17.1%, respectively [26]. In another study, the relative content of lignin decreased from 22.6% to 17% and 19.8% after biotreatment of corn stover with Trametes hirsute and Myrothecium roridum, respectively [27].…”
Section: Analysis Of Biomass Degradationsupporting
confidence: 74%
See 1 more Smart Citation
“…Both the adapted and parental strains reduced the cellulose mass fraction by only about 3%. Similar levels of microbially-induced degradation have been observed by others; for example, using chemical composition analysis of rice straw, Sheng et al (2018) demonstrated that lignin removal was up to 22.4%, and cellulose and hemicellulose loss was 13.3% and 17.1%, respectively [26]. In another study, the relative content of lignin decreased from 22.6% to 17% and 19.8% after biotreatment of corn stover with Trametes hirsute and Myrothecium roridum, respectively [27].…”
Section: Analysis Of Biomass Degradationsupporting
confidence: 74%
“…In conventional physicochemical pretreatment processes, abundant cellulose and hemicellulose loss is inevitable. By comparison, during biological pretreatment, the degradation characteristics of lignocellulose are dependent on the different microbes adopted [26]. The degradation results reported here do appear to demonstrate that the adaptive strain of the Geobacillus sp.…”
Section: Analysis Of Biomass Degradationmentioning
confidence: 49%
“…For the present composting method, WS, RS, CC, and CS are probably better suited for A. bisporus production, while over-fermentation, or the low N content of C and B will lead to poor production of A. bisporus. Sheng et al (2018) showed that the structure of pretreated RS was severely destroyed, and more cracks and large holes were observed with the extension of fermentation time through scanning electron microscopy(SEM). Shahryari et al (2018) found that high intensity fungal growth led to larger accessible surface area and structural destruction in the wheat straw observed by SEM.…”
Section: Discussionmentioning
confidence: 99%
“…Agricultural straws (AS) are organic agricultural residues produced at a global rate of 2-4 × 10 9 t per year, which is 1.4 times the annual crop yield (Smil, 1999). AS comprise mainly of lignocellulosic biomass, most of which is used for combustion in China (Sheng et al, 2018). Until 2018, the amount of AS had reached 886 million tons in China.…”
Section: Introductionmentioning
confidence: 99%
“…The world's largest renewable resource, lignocellulosic biomass consisting primarily of cellulose (30–50%), hemicellulose (20–30%) and lignin (20–30%), has been successfully explored for the production of various value‐added products. Bioconversion of lignocellulosic biomass for the production of biofuels such as ethanol, butanol and biohydrogen has been successfully achieved on a laboratory as well as an industrial scale . Onion is an important vegetable crop cultivated worldwide and has become second topmost horticultural crop.…”
Section: Introductionmentioning
confidence: 99%